2008
DOI: 10.1111/j.1600-0609.2007.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐line therapies for immune thrombocytopenic purpura: re‐evaluating the need to treat

Abstract: Immune thrombocytopenic purpura (ITP) can be challenging to both diagnose and treat: despite the ability to detect anti-platelet antibodies, the diagnosis of ITP remains one of exclusion. Management of ITP is similarly difficult as many therapies pose potential risks that may be worse than the disease. It has been generally agreed that bleeding - not platelet count - should be the rationale for treatment. Despite the absence of prospective, controlled studies, there is consensus that bleeding risks are signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…ITP is preceded by infection in 60-80 % cases. Steroids and intravenous immunoglobulins are used as the first line treatment of immune thrombocytopenia, while immunosuppressive drugs and monoclonal antibodies are applied in refractory cases and splenectomy in chronic ITP (Rodeghiero 2008;Tarantino and Goldsmith 1998;Shad et al 2005;Blanchette et al 1994). Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) are DNA viruses belonging to the Herpesviridae family.…”
Section: Introductionmentioning
confidence: 99%
“…ITP is preceded by infection in 60-80 % cases. Steroids and intravenous immunoglobulins are used as the first line treatment of immune thrombocytopenia, while immunosuppressive drugs and monoclonal antibodies are applied in refractory cases and splenectomy in chronic ITP (Rodeghiero 2008;Tarantino and Goldsmith 1998;Shad et al 2005;Blanchette et al 1994). Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) are DNA viruses belonging to the Herpesviridae family.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroids have been widely recognized as first-line therapy in patients with ITP [17]. Recently, some reports have shown that high-dose dexamethasone (HD-DXM) might be a promising alternative to prednisone as a first-or second-line therapy in adult ITP patients [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The balance of IL-18/IL-18BP plays a role in progression of ITP. 10 Glucocorticoids (GC) have been widely recognized as the most appropriate first-line treatment for ITP, 11 even if the best therapeutic approach is still a matter of debate. Recently, highdose dexamethasone (HD-DXM) in 4-day cycles has proven its clinical efficacy in the treatment of ITP.…”
Section: Introductionmentioning
confidence: 99%